Membangun Komunikasi dengan Keterlibatan Orang Tua dan Guru untuk Kemandirian Siswa - Aisyah Nur Azizah,; Aulia Najwa Afifah,; Suparmi, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Essentially, good student academic achievement must possess one of the following elements, one of which is student independence. Building student independence is paramount in developing character relevant to today's education. One way to foster this character is through communication between parents and teachers to foster student independence. This study aims to demonstrate the influence of parent-teacher communication on fostering student independence. Of the journals reviewed, 14 met the research's relevance level. The results show that organized communication between parents and teachers has a positive impact on the development of student independence. Furthermore, it is also a key factor in encouraging students' enthusiasm for learning, enabling them to develop and achieve academic and non-academic achievements.